Le Refus de l’hybridité culturelle chez les femmes musulmanes en France et en Grande-Bretagne : repli communautaire ou esquisse d’un projet politique ? - Nadia Kiwan (Cahiers du MIMMOC)
This article is divided into three parts. The first part offers a record of scientific works using hybridity. The second part explores the criticisms aimed at that concept. Finally the third part offers an extension of the debate on hybridity. Indeed, instead of conceptualising that concept in terms of individuals, actors or groups of actors, this article will attempt to consider hybridity in relation with the public sphere defined as a complex public space where political coalitions may be created on the basis of seemingly diverging or indeed conflicting interests. This article draws on recent examples of such coalitions, on both sides of the Channel.